Systematic preoperative approach for bariatric surgery, perioperative results, and economic impact - Freire-Moreira, Iolanda; Sanchez-Conde, Maria Pilar; Sousa, Gilles Barreira-de; Garrido-Gallego, Maria Isabel; Rodríguez-López, José María; Juárez-Vela, Raúl; Bragado, Juan Alonso; Carretero-Hernández, Marta; Vargas-Chiarella, Carlos Ricardo; Calderón-Moreno, Jesús; Lorenzo-Gómez, María Fernanda; Vaquero-Roncero, Luis Mario (Frontiers in Public Health, 2024)
Obesity is a complex systemadc condidon, involving numerous anatomical and metabolic changes. Therefore, a comprehensive preoperadve assessment is essendal for each padent contempladng bariatric surgery. This study presents the findings of a proposed protocol designed to streamline the pre-anesthesia consultadon process. Our aim was to compare the efficiency and costs of consults guided by the protocol with those conducted without a specific strategy. Secondary outcomes assessed included postoperadve length of hospital stay and surgical duradon. We conducted a retrospecdve cross-secdonal analysis involving 206 clinical cases. Stadsdcal analyses, including chi-square, Student's t-test, and Mann-Whitney U test, were udlized based on the type of variables. Results showed a significant reducdon in costs, pre-anesthesia consultadon duradon, dme spent in the recovery unit, and the need for referrals. However, no stadsdcally significant differences were observed in the delay before surgery and length of hospital stay in days. In conclusion, this algorithm offers a promising approach to opdmizing perioperadve management for bariatric surgery, demonstradng effecdveness in cumng costs and reducing the need for referrals.